2004
DOI: 10.1038/sj.onc.1208098
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and type IV collagen activate ERα AF-1 by c-Src pathway: effect on breast cancer cell motility

Abstract: The expression of estrogen receptor alpha (ERa) is generally associated with a less invasive and aggressive phenotype in breast carcinoma. In an attempt to understand the role of ERa in regulating breast cancer cells invasiveness, we have demonstrated that cell adhesion on fibronectin (Fn) and type IV Collagen (Col) induces ERamediated transcription and reduces cell migration in MCF-7 and in MDA-MB-231 cell lines expressing ERa. Analysis of deleted mutants of ERa indicates that the transcriptional activation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
(50 reference statements)
1
27
0
Order By: Relevance
“…Taken together with the recent finding that ER activation contributes to inhibit cell movement in MCF7 cells (Sisci et al, 2004), this raised questions as to the generality of the AhRmediated effects documented here. However, the well-differentiated HepG2 hepatocarcinoma cells, which do not respond to estrogens, responded to AhR ligand treatment in a way similar to MCF7 cells (Supplementary Figure 3).…”
Section: Promigratory Action Of Ahr Transcription Factor M Diry Et Almentioning
confidence: 69%
“…Taken together with the recent finding that ER activation contributes to inhibit cell movement in MCF7 cells (Sisci et al, 2004), this raised questions as to the generality of the AhRmediated effects documented here. However, the well-differentiated HepG2 hepatocarcinoma cells, which do not respond to estrogens, responded to AhR ligand treatment in a way similar to MCF7 cells (Supplementary Figure 3).…”
Section: Promigratory Action Of Ahr Transcription Factor M Diry Et Almentioning
confidence: 69%
“…Others have reported that collagen IV stimulates a variety of fundamental functions in MCF-7 cells, such as proliferation, STAT5 signaling, estrogen receptor alpha signaling, src kinase activity and matrix metalloprotease 5 secretion (Cortes-Reynosa et al, 2008;Hirtenlehne et al, 2002;Robledo et al, 2005;Sisci et al, 2004). Likewise, collagen IV specifi cally stimulated chemotaxis of MCF-7 cells towards IGF-1 (Doerr and Jones, 1996).…”
Section: Discussionmentioning
confidence: 92%
“…It is also clear that the subcellular localization of p130Cas is strongly correlated with migration (Fonseca et al, 2004) and in this context it is interesting to note that BCAR3/ AND-34 has been proposed to be required for localization of p130Cas at ruffling membranes (Riggins et al, 2003). Finally, it has been suggested that there may be an auto-regulatory loop between integrins-FAK-c-Src and the ER that inhibits cell migration, but in response to constitutive activation of c-Src, the effects of c-Src become dominant and promote cell migration (Sisci et al, 2004). Possibly, therefore further sustained activation of Src in MCF-7 cells following chronic exposure to tamoxifen may similarly weigh the balance in favour of a pro-migratory phenotype.…”
Section: Discussionmentioning
confidence: 98%